Effects of Tiba and Rhizobium Application on Growth, Yield and Biochemical Components of Brri Dhan-55 (Oryza Sativa L.) (Bangladesh Journal of Botany, 2021)
Effects of TIBA (10, 25, 50 ppm) and Rhizobium inoculation on growth, yield and biochemical components of BRRI Dhan-55 were investigated. Results showed that application of 10 ppm TIBA produced tallest plant, higher number of tillers and leaves per plant although statistically identical to control. The Rhizobium and TIBA treatments had mostly retarding effects on dry weight of leaves, shoots and roots where the lowest values was obtained from Rhizobium application. Leaf area ratio was positively affected by TIBA and Rhizobium treatments except due to 10 ppm where, significantly maximum value was noted from Rhizobium treatment. Specific leaf weight, relative growth rate and net assimilation rate were negatively responded following all treatments and the least value was also recorded from Rhizobium treatment in each cases. Yield attributes and yield of BRRI Dhan-55 were both positively and negatively influenced by Rhizobium and TIBA treatments. The highest harvest index was found in Rhizobium treated plants. The only increase in yield per plant due to 10 ppm TIBA was 2.48 % over the control but statistically similar to control. Results showed that Rhizobium inoculation had showed lowest value in protein content of leaves and seeds. Application of TIBA treatments had significant positive effects on protein content of leaves at flowering stage. However, the influence was rather negative at both tillering and grain filling stages. The 25 ppm TIBA resulted significantly maximum protein content of seeds followed by 10 ppm.Bangladesh J. Bot. 50(4): 1181-1189, 2021 (December)